2002
DOI: 10.1093/annonc/mdf125
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (COX-2), aromatase and breast cancer:a possible role for COX-2 inhibitors in breast cancer chemoprevention

Abstract: Interest in chemoprevention in oncology using suppressants of prostaglandin (PG) synthesis has been stimulated by epidemiological observations that the use of aspirin and other non-steroidal inflammatory drugs (NSAIDs) is associated with reduced incidence of some cancers, including cancer of the breast. The main target of NSAID activity is the cyclooxygenase (COX) enzyme. Two isoforms of COX have been identified: COX-1, the constitutive isoform; and COX-2. the inducible form of the enzyme. COX-2 can undergo ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 66 publications
2
80
0
3
Order By: Relevance
“…The potential anti-cancer effect of aspirin has been hypothesised to be, in part, mediated through suppression of oestrogen biosynthesis [35,36], but similar to our study, two previous cohort studies found no difference in associations by hormone receptor status [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…The potential anti-cancer effect of aspirin has been hypothesised to be, in part, mediated through suppression of oestrogen biosynthesis [35,36], but similar to our study, two previous cohort studies found no difference in associations by hormone receptor status [10,17].…”
Section: Discussionsupporting
confidence: 88%
“…Inhibition of the COX-2 enzyme and attenuation of the consequential carcinogenic effects of overexpression with increased prostaglandin production (inhibition of apoptosis, stimulation of neo-angiogenesis, upregulation of intra-tumoral CYP19 aromatase; Davies et al, 2002) at this stage has the potential to prevent progression to invasion.…”
Section: Discussionmentioning
confidence: 99%
“…65 A retrospective review of breast cancer patients undergoing mastectomy suggested that intraoperative ketorolac use was associated with decreased cancer recurrence. 66 Impact of anesthesia for cancer surgery 1253 RCT -randomized controlled trial.…”
Section: Agents and Techniques Directly Implicated In Immunosuppressimentioning
confidence: 99%
“…65 Une étude rétrospective chez des patientes ayant un cancer du sein subissant une mastectomie a suggéré que l'utilisation peropératoire de kétorolac était associée à un taux de récidive moindre du cancer. 66 …”
Section: Molécules Et Techniques Directement Impliquées Dans L'immunounclassified